2001
DOI: 10.1007/s004640000392
|View full text |Cite
|
Sign up to set email alerts
|

Obesity adversely affects the outcome of antireflux operations

Abstract: Obesity adversely affects the long-term success of antireflux operations. Although athoracotomy provides optimal exposure of the hiatal structures in obese patients, a transthoracic approach was associated with a higher recurrence rate than LNF. Given the high failure rate of antireflux operations in obese patients, intensive efforts at sustained weight loss should be made before consideration of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
138
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(154 citation statements)
references
References 17 publications
2
138
3
6
Order By: Relevance
“…However, a small number of patients from all the groups postoperatively graded themselves as Visick III or IV on account of recurrent reflux symptoms, or side effects of the anti-reflux surgery (gas bloat, postprandial fullness, early satiety, inability to belch and dysphagia). 9 Nevertheless, our findings do not support the premise that obesity is the cause of marked increase in failure rate as reported by Perez et al 4 Follow-up of patients is a difficulty encountered in many studies, as patients either refuse or become uncontactable for a variety of reasons. Similar to the problems Smith et al 19 encountered, we have found it difficult to obtain meaningful numbers of patients for follow-up after 1 year.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, a small number of patients from all the groups postoperatively graded themselves as Visick III or IV on account of recurrent reflux symptoms, or side effects of the anti-reflux surgery (gas bloat, postprandial fullness, early satiety, inability to belch and dysphagia). 9 Nevertheless, our findings do not support the premise that obesity is the cause of marked increase in failure rate as reported by Perez et al 4 Follow-up of patients is a difficulty encountered in many studies, as patients either refuse or become uncontactable for a variety of reasons. Similar to the problems Smith et al 19 encountered, we have found it difficult to obtain meaningful numbers of patients for follow-up after 1 year.…”
Section: Discussioncontrasting
confidence: 84%
“…There was no weight limit on those operated on in this study; therefore, there was no limit on the BMI. Perez et al 4 supported the idea that intensive efforts at weight loss should be maintained pre-operatively since an increased BMI adversely affects surgical outcome. However, the value of weight reduction pre-operatively remains unproven and, in reality, may prove to be difficult and unrealistic to achieve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,2,5,7,8,11,13 Careful selection has been recommended for patients with GERD 2,14 and also when introducing other advanced laparoscopic procedures in a nonacademic community hospital setting to ensure excellent outcomes. 15 Some studies have shown poor long-term outcomes after laparoscopic Nissen fundoplication in obese patients, 16 and on this basis no patients with a BMI greater than 35 were offered surgery in the present study. Once good outcomes are established the indications can be broadened to include patients with a BMI greater than 35.…”
Section: Discussionmentioning
confidence: 73%
“…The management of GORD in obese patients remains contentious with no consensus or published guidelines. Data are conflicting regarding the long-term efficacy of fundoplication in obese individuals compared with normal weight counterparts [18][19][20][21][22] . Nevertheless, most surgeons would agree that treatment of GORD in obese and non-obese patients requires different strategies [23] .…”
Section: Introductionmentioning
confidence: 99%